The Effect of Digitalization and the Work Environment on Employee Performance at STPN Yogyakarta - Megananta Renatabumi; Fereshti Nurdiana Dihan (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of digitalization and work environment on employee performance at the National Land College (STPN) Yogyakarta. A quantitative associative research approach was employed, involving 47 employees as respondents. Data were collected through questionnaires, observation, and documentation and analyzed using multiple linear regression, t-test, F-test, Pearson correlation, and coefficient of determination (R²). The results show that digitalization has a significant positive effect on employee performance, with a t-count of 2.940 > t-table 1.680 and a significance value of 0.005 < 0.05. The work environment also has a significant positive effect, with a t-count of 3.980 > 1.680 and a significance value of 0.000 < 0.05. Simultaneously, digitalization and work environment significantly influence employee performance, with an F-count of 49.275 > 3.204 and a significance value of 0.000 < 0.05. The coefficient of determination indicates that both variables explain 69.1% of employee performance, while 30.9% is influenced by other factors. Pearson correlation results indicate strong relationships between digitalization and performance (r = 0.762) and work environment and performance (r = 0.794). These findings highlight the importance of digitalization and a conducive work environment in improving employee performance.